Vessel sealing versus suture ligation for canine ovarian pedicle haemostasis: a randomised clinical trial. (31st January 2015) - Schwarzkopf, I.; Van Goethem, B.; Vandekerckhove, P. M.; de Rooster, H.
Abstract : Vessel sealing (VS) is well established in laparoscopic ovariectomy (OVE) in dogs. The objectives of this study were to evaluate the efficacy of ovarian pedicle haemostasis by VS using a commercially available VS tool in open OVE and compare it with suture ligation (SL). A prospective, randomised clinical trial including 20 female dogs was designed. Open OVE was performed via a standard mid‐line celiotomy by a single surgeon using a standardised protocol. At random, the right ovarian pedicle was sealed (VS) or ligated (SL) whereas the left pedicle was treated by the alternative technique. Surgical times for procedural stages and intra‐operative complications were recorded and statistically evaluated. Total surgical time was 29.28±11.13 minutes (range 12.50–62.13 minutes) and time from identification to removal of the ovary was significantly less when sealing (VS 2.22±0.58 minutes) than when ligating (SL 4.10±1.13 minutes P=0.0001). Intra‐operative complications were rare for both techniques (failure of the electrode of the VS device (n=3); ovarian pedicle haemorrhage due to ligature slippage (n=1)). The results of the current study indicate that ovarian pedicle haemostasis achieved by VS is significantly faster than by placement of ligatures without appearing to compromise safety.